2003
DOI: 10.1093/geronb/58.3.s151
|View full text |Cite
|
Sign up to set email alerts
|

Creating Continuity Through Mutual Assistance: Intergenerational Reciprocity in Four Ethnic Groups

Abstract: Social exchange can be viewed not only as a means by which those who are old maintain power but as a major vehicle for perpetuating continuity across the generations. When social exchange breaks down, elders suffer from loss of power as expressed through role loss. Elders must have a negotiable commodity to exchange as well as the flexibility to adjust to changes in the extended family. Maintaining continuity of the family in the face of disruptive threats poses a particular challenge for elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 23 publications
2
57
0
9
Order By: Relevance
“…Multiple studies have shown that extended family involvement is more important among African Americans than whites. 15 African American family child-rearing styles more typically stress interdependence and respecting the extended family system. 16 Extended family is not only a strategy for meeting the daily needs of the family but commits family resources to transitional crisis situations-as exemplified in the diagnosis of a chronic illness or injury.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that extended family involvement is more important among African Americans than whites. 15 African American family child-rearing styles more typically stress interdependence and respecting the extended family system. 16 Extended family is not only a strategy for meeting the daily needs of the family but commits family resources to transitional crisis situations-as exemplified in the diagnosis of a chronic illness or injury.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in shared households also have opportunities to exchange daily support (Becker et al, 2003). …”
Section: Cross-national Differences In Parental Involvement With Collmentioning
confidence: 99%
“…Mutual aid has been demonstrated to be an important part of self-care strategies in the management of illness. 40,41 Similarly, spirituality is central: the Black church has developed and sustained itself as a vital institution for the survival and advancement of African Americans, who were refused access to the institutional life of White American society, and who rejected the hypocrisy of White Christianity. 42,43 The church continues to fulfill many functions of social organization, such as education, social welfare, civic duties, and business enterprises, as well as serving as an outlet for social expression, a vehicle for social protest, and a refuge from racism and discrimination.…”
Section: The Context Of African American Self-carementioning
confidence: 99%